Impact of Indoor Air Quality by Incorporating Agricultural Waste Into Fired Clay Brick - Sarani, Noor Amira; Kadir, Aeslina Abdul; Yusuf, Zaki Muhamad (International Journal of Engineering and Technology, 2018)
The demand for edible oil from all over the world has generated a huge amount of solid waste. Due to that, the problem of disposal method has become a constraint by the authorities. Therefore, this study is focusing on the incorporation of palm kernel shell (PKS) into fired clay brick in terms of indoor air quality assessment. The brick was incorporated with 0% and 5% of PKS and fired at 1050°C with heating rates of 1°C/min. Preliminary analysis was conducted with X-Ray Fluorescence test to determine chemical composition of raw materials used in the study. A further experiment of indoor air quality was obtained by measuring gases emission of total volatile organic compound (TVOC), carbon dioxide (CO2), carbon monoxide (CO), ozone (O3), formaldehyde (HCHO) and particulate matter (PM10) in Walk in Stability Chamber with controlled temperature and relative humidity. All parameters were compared with Industry Code of Practice on Indoor Air Quality standard. The result shows that incorporation 5% of PKS into fired clay brick complied with the standard requirement for use as building materials. As the conclusion, the use of palm kernel shell as clay replacement could reduce the waste disposal in landfills whilst providing low-cost building materials.